Moving Minds: How Physical Activity Shapes Motivation and Self-Concept in School Children - Slobodan Pavlović; Vladan Pelemiš; Marko Badrić; Dalibor Stević; Nebojša Mitrović (Behavioral Sciences)
Background: This study aimed to investigate the differences in motivation and physical self-concept among pupils based on their level of physical activity during physical education classes. Methods: The research encompassed 398 pupils (aged 10 ± 0.3 years), including 211 boys and 187 girls, divided into three groups according to their level of physical activity during class (Group A—low; Group B—medium; Group C—high). The modified Self-Regulation Questionnaire was used to evaluate pupils’ motivational orientations, while the corresponding subscales of the Self-Perception Profile for Children (SPPC) were employed to measure physical self-concept. Pupils’ physical activity (measured in steps and intensity) during physical education classes was assessed using CoachGear pedometers and Suunto Memory Belt heart rate monitors. Results: The findings revealed significant differences between the groups of pupils of both genders concerning their physical activity levels during early school years. Notably, these differences were more pronounced in boys than in girls. Additionally, it was observed that less active pupils generally exhibited lower levels of motivation as well as lower physical self-concept scores. Conclusion: Pupils with higher levels of physical activity during physical education classes demonstrated greater motivation and a more positive physical self-concept, highlighting the crucial role of engagement in fostering both psychological and physical development. These findings underscore the need for well-structured and engaging physical education programs that support active participation and enhance pupils’ overall well-being.